Structural and functional fetal cardiac imaging using low field (0.55 T) MRI - Zhang, Charlie Yuli; Cleri, Michela; Woodgate, Tomas; Ramirez Gilliland, Paula; Bansal, Simi; Aviles Verdera, Jordina; Uus, Alena U.; Kyriakopoulou, Vanessa; St Clair, Kamilah; Story, Lisa; Hall, Megan; Pushparajah, Kuberan; et al. (Frontiers in Pediatrics, 2024)
Purpose: This study aims to investigate the feasibility of using a commercially available clinical 0.55T MRI scanner for comprehensive structural and functional fetal cardiac imaging. Methods: Balanced steady-state free precession (bSSFP) and phase contrast (PC) sequences were optimized by in utero studies consisting of 14 subjects for bSSFP optimization and 9 subjects for PC optimization. The signal-to-noise ratio (SNR) of the optimized sequences were investigated. Flow measurements were performed in three vessels, umbilical vein (UV), descending aorta (DAo), and superior vena cava (SVC) using the PC sequences and retrospective gating. The optimized bSSFP, PC and half-Fourier single shot turbo spin-echo (HASTE) sequences were acquired in a cohort of 21 late gestation-age fetuses (>36 weeks) to demonstrate the feasibility of a fetal cardiac exam at 0.55T. The HASTE stacks were reconstructed to create an isotropic reconstruction of the fetal thorax, followed by automatic great vessel segmentations. The intra-abdominal UV blood flow measurements acquired with MRI were compared to ultrasound UV free-loop flow measurements. Results: Using the parameters from 1.5T as a starting point, the bSSFP sequences were optimized at 0.55T, resulting in a 1.6-fold SNR increase and improved image contrast compared to starting parameters, as well as good visibility of most cardiac structures as rated by two experienced fetal cardiologists. The PC sequence resulted in increased SNR and reduced scan time, subsequent retrospective gating enabled successful blood flow measurements. The reconstructions and automatic great vessel segmentations showed good quality, with 18/21 segmentations requiring no or minor refinements. Blood flow measurements were within the expected range. A comparison of the UV measurements performed with ultrasound and MRI showed agreement between the two sets of measurements, with better correlation observed at lower flows.We demonstrated the feasibility of low-field (0.55T) MRI for fetal cardiac imaging. The reduced SNR at low field strength can be effectively compensated for by strategically optimizing sequence parameters. Major fetal cardiac structures and vessels were consistently visualized, and flow measurements were successfully obtained. The late gestation study demonstrated the robustness and reproducibility at low field strength. MRI performed at 0.55T is a viable option for fetal cardiac examination.